Skilled migrant workplace integration: the choice between pragmatism and critical realism approaches. Issue 3 (27th May 2022) - Tran, Thi Tuyet; Cameron, Roslyn; Montague, Alan; Nuenjohn, Nuttawuth; Fan, Shea
ABSTRACT : This article provides a rationale for adopting the critical realism (CR) instead of pragmatism paradigm when researching skilled migrants' (SMs) workplace integration in Australia. While the extant SM literature has provided an abundance of 'explanations' reflecting the difficulties SMs face, it appears almost impossible for SMs to overcome some challenges such as discrimination or lack of local work experience. However, there is not a sufficient explanation for why many SMs have successfully integrated within the host labour market despite facing such difficulties. This study was designed to challenge what may have been 'taken-for-granted' in the literature and explore the causal relationship behind the SMs' difficulties and success. The CR paradigm provides a new way to examine the problems SMs face and their strategies to overcome such issues. It also empowers researchers to look beyond the empirical layer of evidence and explore how and why things happen the way they do.